Qualitative Study of Reasons for Effective Human Resource Information Systems in the Health Sector of a Southern African Country - Udekwe, Emmanuel; Iwu, Chux Gervase (Journal of Ecohumanism, 2025)
Human Resource Information Systems (HRIS), as mechanisms for human resource management, are recognised to facilitate transformative change within organisations. In the context of the health sector, effective human resource performance is essential for organisational development and to achieve the United Nations (UN) Sustainable Development Goals (SDGs). It is noteworthy that, despite a focus on research and development regarding HRIS within the health sector, the precise mechanisms through which such systems can enhance sustainability in Southern African countries, such as South Africa, remain ambiguous. This research underscores the importance of implementing effective HRIS in the health sector. The research employed qualitative methodologies, utilising interviews as the primary data collection tool. Multiple hospitals expressed their interest in participation, and the Department of Health of the Southern African country granted the necessary approvals. A purposive sampling approach was employed to select the participants from the hospitals. The research adopted an inductive approach within an interpretive paradigm. To ensure the validity of the research instrument, psychometric property testing was conducted. The findings indicate that the implementation of HRIS within the health sector is partially comprehended. Furthermore, several reasons that hinder the effectiveness of HRIS were identified, including lack of familiarity, resistance, perception, guidance and issues related to security. The research provides recommendations for overcoming these barriers to enhance the efficacy of HRIS in the health sector, thereby fostering employee commitment and future research.